Pengaruh Kebijakan Pemisahan Terhadap Laba Pada Bank BNI Syariah - Andreyanto Ramdani (Faculty of Economic and Business, 2015)
The Impact of Spin-Off Policy on Profitability in Bank of BNI ShariaThe purpose of this paper is to analyze whether the spin-off policy which is based on law no. 21 in 2008 had an influence on profit of Bank of BNI Syariah period 2007-2015. This study uses multiple regressions using dummy equation to analyze the effect of the spin-off policy to profit at Bank of BNI Syariah. The variable used is a dummy variable spin-off, as well as put some internal factors such Third Party Fund, BOPO. The results shows that the dummy variable spin off and BOPO have an influence on the amount of profit and DPK has no effect on the amount of earnings at Bank of BNI Syariah. These results shown that the spin-off policy BNI Syariah done rightDOI: 10.15408/etk.v14i1.2261